Peningkatan Skill Pengelolaan Coffeshop Sederhana Bagi Santri Pondok Pesantren Al Asror Kota Semarang - Satsya Yoga Baswara; Ratieh Widhiastuti (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
Strengthening the entrepreneurial spirit at Al Asror Islamic boarding school in Semarang is a top priority in the digital age. The UNNES service team will organize cafe management training for teenage students. This effort is a response to service partner issues that require attention from a variety of parties, both internal to the boarding school and UNNES. This training program follows the previous training on artisanal coffee processing in Islamic boarding schools in 2022. We will explore the potential of students who participated in previous training courses, strengthen their entrepreneurial attitude, and gain a deeper understanding of Asatidz's board leadership style. Expected outcomes of this community service program include publications in recognized national magazines, feature stories in print/electronic media, and feature videos of translation activities. service. All this is aimed at actively contributing to the formation of students' entrepreneurial attitudes and maintaining the uniqueness of Al Asror Islamic Boarding School, while remaining in step with the times.